2019
DOI: 10.1007/s40495-019-00202-8
|View full text |Cite
|
Sign up to set email alerts
|

Usnic Acid Derivatives as Cytotoxic Agents Against Cancer Cells and the Mechanisms of Their Activity

Abstract: Purpose of Review This article summarises recent research on modifications of the structure or formula of usnic acid (UA), a lichen secondary metabolite, in order to obtain derivatives with higher bioavailability, potency and selectivity against cancer cells and presents the current knowledge on the mechanisms of action of such compounds. Recent Findings Numerous approaches have been undertaken to improve bioactivity of UA concerning its use as an anticancer drug. Among them, the synthesis of UA salts or compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 55 publications
(86 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the correlation analysis also found that usnic acid might be responsible from the reduced tumor cell viability, apoptosis, and cell cycle inhibition. In contrast to protocetraric acid, usnic acid as lead compound of F. caperata , has various well-known activities ( Cocchietto et al., 2002 ; Ingolfsdottir, 2002 ; Guzow-Krzemińska et al., 2019 ). In line with our findings, it was already shown that usnic acid induce a G1-Block in the gastric cancer cell line BGC823, in A549 lung carcinoma cells ( Singh et al., 2013 ), in the breast cancer cell line MCF-7, and in the prostate adenocarcinoma cell line LNCap ( Eryilmaz et al., 2018 ; Geng et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the correlation analysis also found that usnic acid might be responsible from the reduced tumor cell viability, apoptosis, and cell cycle inhibition. In contrast to protocetraric acid, usnic acid as lead compound of F. caperata , has various well-known activities ( Cocchietto et al., 2002 ; Ingolfsdottir, 2002 ; Guzow-Krzemińska et al., 2019 ). In line with our findings, it was already shown that usnic acid induce a G1-Block in the gastric cancer cell line BGC823, in A549 lung carcinoma cells ( Singh et al., 2013 ), in the breast cancer cell line MCF-7, and in the prostate adenocarcinoma cell line LNCap ( Eryilmaz et al., 2018 ; Geng et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, these studies revealed the importance of β-triketone moiety for UA activity [22,23]. Since then, different approaches have been undertaken to improve its bioactivity, including synthetic modifications of UA's structure [24].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the co-treatment of lobarstin, a secondary metabolite isolated from Stereocaulon alpinum, enhanced toxicity of temozolomide when used in GBM T98G cells [19]. In another study, the ketamine derivatives of (+)-usnic acid had significant cytotoxicity against human GBM-astrocytoma cell line U87MG, and a novel N-heterocyclic derivative of (+)-usnic acid was found to be even more active than temozolomide [20]. These findings justify further studies exploring the possible applications of lichenochemicals in brain tumor treatment.…”
Section: Introductionmentioning
confidence: 99%